Electrochemiluminescence Based Enzymatic Urea Sensor Using Nanohybrid of Isoluminol‐gold Nanoparticle‐graphene Oxide Nanoribbons. Issue 4 (22nd November 2016) - Ismail, Nur Syakimah; Hoa, Le Quynh; Huong, Vu Thi; Inoue, Yuki; Yoshikawa, Hiroyuki; Saito, Masato; Tamiya, Eiichi
Abstract: This study evaluates on the possibility of using gold nanoparticles functionalized with the luminol derivative N‐(aminobutyl)‐N‐(ethylisoluminol) (ABEI) and hybridized with graphene oxide nanoribbons on a carbon based screen‐printed electrode (ABEI‐AuNP‐GONR/SPE) as an enzymatic electrochemiluminescence (ECL) urea sensor. The electrocatalytic activity and ECL intensity of ABEI‐AuNP‐GONR/SPE were found to increase proportionally with the concentration of urea in the analyte sample, owing to the rise in pH value. These phenomena are attributed to increased formation of luminol monoanion precursors for further electrochemical oxidation, which in turn produce either luminol radicals or excited 3‐amino‐phthalate molecules. The luminescence is most likely caused by the interaction of luminol radicals with superoxide radicals formed from dissolved oxygen. The sensitivity of our sensor was determined to be 170.58 mM −1 and 16.23 mM −1 for urea concentrations from 2 to 5.82 mM and from 5.82 to 30 mM, respectively, covering the normal urea level in human blood. Abstract :